The differences between Serbian and Icelandic organizational cultures - Desnica, Bojan, 1975- (2013)
In the time of global economy, culture is viewed as a general social concept, but holders of global culture are people with different national and cultural identity. On the other hand, companies are developing an organizational culture with the aim of integrating the values and the steering behavior of employees towards common business goals. In this regard, companies have a continuous job to manage cultural diversity. Globalization means the economic, political and cultural process, driven by the desire of large corporations to enter new markets. Organizational culture differs between companies and countries. In terms of global connectivity and market challenges companies are becoming more numerous and complex. Organizational culture is an important factor in the success of the company. This research covers the difference in two national cultures, Icelandic and Serbian, along with the differences in organizational cultures. The main reason for this research is that the author of this text is born in Serbia and has spent the last twelve years in Iceland. The research starts with looking at the national cultures and how they can influence the business cultures. The business cultures are analyzed with the Hofstede dimensions ,and then compared to see the similarities and differences between the two cultures. Actavis is a leading global pharmaceutical company working in over 40 countries around the world. These countries are as different as they are many and I thought it would be very interesting to take a deeper look at two of them situated in Iceland and in Serbia. The research question we set out to answer is: What is the difference in the Actavis business culture in Serbia and Iceland? The results showed that there are significant differences and similarities between national cultures of Iceland and Serbia. Despite the fact that these two countries never used to have economic or any relation there are organizational similarities through within each dimension of national culture. Serbian national culture could ...